Perancangan Interior Museum Jakarta Fashion Week - Sriti Mayang Sari, Esther Patricia Wirantono (Intra, 2014)
The advancement of fashion industry is growing rapidly, and every single society is fond of it. Attention is given on formal, informal, and even casual outfit. With the presence of Jakarta Fashion Week every year, people are able to see the diversity of fashionâs evolution. Hence, this Jakarta Fashion Week Museum Interior Design is expected to provide knowledge and educate the public visitors regarding the evolution of fashion trends in Indonesia. Moreover, it conveys a message to the world that Indonesia is able to compete in global fashion industry. The Harmony of Geometrical Shapes concept is what this design will put forth. Thus, the will-be-used interior is more towards simple and geometric formation. This geometric formation is used in order to make the displayed fashion looks more prominent and attractive. Supporting facilities in this design are the lobby, gift shop, retail shop, cafÃ©, museum display and show area, which will make visitors comfortable.